Montmorillonite for selective hydroxyalkylation of p-cresol - Garade, Ajit C.; Mate, Vivek R.; Rode, C. V. (Applied Clay Science, 2009)
Performances of montmorillonite titanium silicate (TS-1) and dodecatungstophosphoric acid (DTP) were compared for the hydroxyalkylation of p-cresol into dihydroxydiarylmethane (DAM). Ammonia TPD studies of various catalysts showed that an appropriate combination of both strong and weak acid sites of montmorillonite was mainly responsible rather than only the stronger acidity of bulk DTP for its highest catalytic activity for selective hydroxyalkylation of p-cresol to DAM. The selectivity to DAM could be enhanced by adjusting reaction conditions like mole ratio of p-cresol to formaldehyde, reaction temperature, catalyst concentration, solvent and reaction time. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Ammonia TPD; Dihydroxydiarylmethane; Hydroxyalkylation; Montmorillonite; Solid acids

Selectivity tailoring in liquid phase oxidation over MWNT-Mn3O4 nanocomposite catalysts - Biswal, Mandakini; Dhas, Vivek V.; Mate, Vivek R.; Banerjee, Abhik; Pachfule, Pradip; Agrawal, Kanika L.; Ogale, Satishchandra B.; Rode, Chandrashekhar V. (Journal of Physical Chemistry C, 2011)
Highly selective multiwalled nanotubes (MWNT)-Mn3O4 nano-composite catalyst was designed for liquid phase oxidation of p-cresol, which gave highest selectivity of 90% to the first step oxidation product, p-hydroxy benzyl alcohol. Mn3O4 nanoparticles and MWNT-Mn3O4 nanocomposites were synthesized by coprecipitation route using mixed precursors under controlled conditions. The phase purity of Mn3O4 and the formation of MWNT-Mn3O4 nanocomposites were confirmed by X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectroscopy. High-resolution transmission electron microscopy revealed the selective exposure of (101) and (001) planes of Mn3O4 nanoparticles in the MWNT-Mn3O4 composite, while lowering in oxidizing capacity of MWNT-Mn3O4 nanocomposite confirmed by cyclic voltametry was due to incorporation of electron rich MWNT. Thus, selectivity tuning of the new material (MWNT-Mn3O4 nanocomposite) was found to be due to alteration in both geometric as well as electronic properties. A plausible reaction pathway also has been proposed involving the predominant role of nucleophilic lattice oxygen (O2-) species due to exposure of particular crystal planes giving highest selectivity to p-hydroxy benzyl alcohol.

Heterogeneous Co3O4 catalyst for selective oxidation of aqueous veratryl alcohol using molecular oxygen - Mate, Vivek R.; Shirai, Masayuki; Rode, Chandrashekhar V. (Catalysis Communications, 2013)
Nano-structured, spinel Co3O4 catalyst was developed for the aqueous phase oxidation of veratryl alcohol, which showed the highest conversion of 85% with 96% selectivity to veratryl aldehyde. The co-existence of Co3+ and Co2+ species in the octahedral and tetrahedral positions respectively, was confirmed by XPS, cyclic voltammogram, TPR and TPO characterization. The rod-like morphology of Co3O4 catalyst was confirmed by HRTEM. The effects of various reaction parameters namely, catalyst concentration, temperature and partial oxygen pressure on conversion and selectivity patterns were also studied for the oxidation of veratryl alcohol. This catalyst also showed an excellent stability as evidenced by successful reusability for three times. (C) 2012 Published by Elsevier B.V.
Keywords: Co3O4; Cyclic voltammogram; Liquid phase oxidation; Molecular oxygen; Veratryl alcohol; XPS

Effect of preparation parameters on characterization and activity of Co3O4 catalyst in liquid phase oxidation of lignin model substrates - Mate, Vivek R.; Jha, Ajay; Joshi, U. D.; Patil, K. R.; Shirai, M.; Rode, C. V. (Applied Catalysis A-General, 2014)
The nano structured spinel cobalt oxide (Co3O4) was prepared via simple co-precipitation method and its catalytic activity was evaluated for the liquid phase aerobic oxidation of lignin sub structure compounds such as veratryl alcohol. Catalyst preparation parameters influenced its morphology eventually affecting its oxidation activity. Thus, nano rod shaped CO3O4 catalyst showed 75% and 38% conversion of veratryl alcohol with complete selectivity to veratryl aldehyde in toluene and water, respectively, under base free condition. The influence of reaction conditions, such as temperature, oxygen pressure and catalyst loading was studied to obtain the optimum product yield and selectivity to the desired product. Furthermore, oxidation of various sub-structures of lignin model compounds was also studied over the same catalyst which was found to be in the following order: secondary alcohol >di-substituted > tri-substituted > monosubstituted > non-substitution. The stability of the catalyst was confirmed by its successful recycle for three times. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: Coniferyl alcohol; Nano Co3O4; Sinapyl alcohol; TPR; Veratryl alcohol

Architecture of 2D MoS2 nanosheets and 3D CdMoS4 marigold flowers: consequence of annealing on field emission performance - Kadam, Sunil R.; Suryawanshi, Sachin R.; Panmand, Rajendra P.; Mate, Vivek R.; More, Mahendra A.; Late, Dattatray J.; Kale, Bharat B. (Microporous and Mesoporous Materials, 2016)
Herein, we report the field electron emission investigations on template free solvothermally synthesized layered MoS2 nanosheets as well as novel phase of CdMoS4 nanoflowers at the base pressure of similar to 1 x 10(-8) mbar. The turn-on field, threshold field and maximum emission current densities for both MoS2 and CdMoS4 are strongly influenced by thermal annealing in inert atmosphere. The turn on field, required to draw emission current density of 1 mu A/cm(2) is found to be 5.8 and 3.2 V/mu m for pristine and annealed MoS2 at 400 degrees C. In case of as prepared and annealed CdMoS4 sample the turn on field values are found to be similar to 6.2 and 5.0 V/mu m, respectively. The emission current versus time (I-t) plot measured at the preset current values of similar to 1 mu A for pristine and annealed sample indicates stable operation of the emitter. The emission current fluctuations for annealed sample are observed to be less as compared with the pristine sample due to conditioning of the emitter, thereby showing highly stable nature of emitter. Thus, the present result demonstrates the potential of annealed MoS2 nanosheets and CdMoS4 nanoflowers as an emerging materials for micro/nanoelectronics and flat panel field emission display applications. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: field emission; MoS2 and CdMoS4; Nanoflowers; nanosheets